Diffusion and policy transfer in armed UAV proliferation: the cases of Italy and Germany. (4th March 2019) - Ceccoli, Stephen; Crosston, Matthew
ABSTRACT: In a 2015 policy change, the U.S. State Department released guidelines governing the sale of armed unmanned aerial vehicles (UAVs) to other countries, and several export agreements were signed shortly later. While considerable scholarly effort has been devoted to the impact or consequences of UAV proliferation, few studies have analyzed the actual diffusion process. This article applies the insights from both diffusion theory and policy transfer to examine the various diffusion mechanisms while using the experiences from Italy and Germany to illustrate distinct cases policy convergence and divergence, respectively. While the competition mechanism is typically constrained to policy adopting jurisdictions, evidence on armed UAV diffusion suggests policy transfer decisions can also hinge on competition among exporting jurisdictions. Consequently, we seek to point attention to the interaction between diffusion mechanisms (such as competition) and various domestic conditions, demonstrating that diffusion is neither apolitical nor necessarily neutral in character.